2022
DOI: 10.1111/phn.13051
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity changes among non‐Hispanic Black pregnant women

Abstract: Objective: To examine aerobic physical activity (PA) among non-Hispanic Black pregnant women.Design: Longitudinal prospective cohort study. Sample:A subset of 161 non-Hispanic Black pregnant women from the Midwestern US participating in a larger study completed questionnaires about aerobic physical activity (PA) before pregnancy (reported at 24.46±2.13 weeks gestation), mid-pregnancy (24.46±2.13 weeks gestation), and late pregnancy (31.78±1.95 weeks gestation).Measurements: Aerobic PA was measured using the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 57 publications
1
4
0
2
Order By: Relevance
“…In previous studies, reductions in the PA levels have been reported throughout pregnancy (25)(26) . This decrease had been previously attributed to the reduction in the work-related PA levels that can take place in the second half of pregnancy (27) .…”
Section: Discussionmentioning
confidence: 87%
“…In previous studies, reductions in the PA levels have been reported throughout pregnancy (25)(26) . This decrease had been previously attributed to the reduction in the work-related PA levels that can take place in the second half of pregnancy (27) .…”
Section: Discussionmentioning
confidence: 87%
“…Em estudos anteriores, foram relatadas diminuições da AF ao longo da gestação (25)(26) . Essa diminuição já foi atribuída à diminuição da AF relacionada ao trabalho que pode ocorrer na segunda parte da gestação (27) .…”
Section: Resultados Características Da Amostraunclassified
“…En estudios previos, se han reportado descensos de la AF a lo largo del embarazo (25)(26) . Este descenso ha sido anteriormente atribuido a la disminución de AF relacionada con el trabajo que puede producirse en la segunda parte de la gestación (27) .…”
Section: Discussionunclassified